1989
DOI: 10.1096/fasebj.3.5.2537775
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxylate cycle in the rat liver: effect of vitamin D 3 treatment

Abstract: Evidence for the glyoxylate cycle in the mammalian rat liver was sought. Activity of two unique glyoxylate cycle enzymes, isocitrate lyase and malate synthase, was found in rat liver homogenates. Vitamin D3 treatment of rachitic animals produced a five- and fourfold increase, respectively, in the activity of these enzymes. Vitamin D3 also increased the peroxisomal fatty acid oxidation and the accumulation of glycogen in liver slices in the presence of palmitate. These data suggest that the mammalian rat liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…The same authors have demonstrated induction by VD of peroxisomal -oxidation in rat liver (Davis et al 1989).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The same authors have demonstrated induction by VD of peroxisomal -oxidation in rat liver (Davis et al 1989).…”
Section: Introductionmentioning
confidence: 78%
“…None was upregulated. This was unexpected since Davis et al (1989) reported an increase in peroxisomal palmitate oxidation in rat liver after VD administration (a single dose of 500 IU). There is, however, no actual contradiction with our mRNA assay; enzyme capacity can be modified by other mechanisms such as mRNA stability or enzyme turnover (Horie & Suga 1989).…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have demonstrated that hepatic tissue has several physiological responses to 1,25(OH)2D3 (16)(17)(18)(19)(20)(21)(22)(23)(24)46) and appears to contain high-affinity receptors for this potent hormone (47). General vitamin D deficiency in the rat has been shown to alter hepatic function as manifested by delayed bromosulfthalein clearance and elevated plasma transaminases (16).…”
Section: Identificationmentioning
confidence: 99%
“…Furthermore, this study also noted liver histology changes consistent with periportal necrosis due to vitamin D deficiency. Hepatic isocitrate lyase and malate synthase are also known to be decreased in vitamin D deficiency (46). In addition to these generalized symptoms of vitamin D deficiency, 1,25(OH)2D3 is known to specifically increase hydroxymethylglutaryl CoA reductase activity (18), decrease liver regeneration time independent of calcium (17), regulate the synthesis of hepatic DNA polymerase a (19,20), increase [3H]thymidine incorporation into hepatic DNA (17), and enable regenerating liver cells to make functional ribonucleotide reductase subunits (21).…”
Section: Identificationmentioning
confidence: 99%
“…Vitamin E with its anti-oxidant properties is important for alleviating the effects of cardiac oxidative stress [ 97 , 98 ] by inhibiting lipid peroxidation [ 99 , 100 ], stress signaling pathways [ 101 ] and apoptosis [ 102 , 98 , 101 ]. Regarding vitamin D, although there is not much information about its role in cardiac fatty acid oxidation, it has been associated with increased fatty acid oxidation in other organs such as liver [ 103 ] and bone cartilage [ 104 ]. Thus, vitamin D may have a positive effect on cardiac fatty acid oxidation.…”
Section: Role Of Lipoprotein-carried Vitamins In Cardiac Metabolism Amentioning
confidence: 99%